Pengaruh Pola Asuh terhadap Online Resilience - Isnaini Kumala Firdaus; Estalita Kelly Kelly (Ilmu Psikologi Universitas Yudharta Pasuruan)
Resilience in various studies is seen as a basic force that becomes the foundation of various positive characters in a person. There are several sources of resilience formation according to Gritberg, one of which is parenting. According to Diana Baumbrind there are three types of parenting namely authoritarian parenting, democratic parenting, and authoritarian parenting. This study aims to determine the effect of parenting on online resilience. The research subjects were Students of Yudharta Pasuruan 55 Women and 45 Men from 100 respondents who were met randomly. Data collection used in this study is online resilience scale and parenting scale. This study uses ANOVA 1-way data analysis. The results of the 1-path Anava analysis obtained FoA of 29.432 with F tab 1% 4.61. With this hypothesis which states that there is an effect of parenting on Online Resilience and there are differences in the influence of Authoritarian Parenting, Democratic Parenting and Permissive Parenting towards online resilience.